Ascariasis and protein energy malnutrition among schoolchildren of Monteclaro Elementary School, Miag-ao, Iloilo. - Berlin, Nellisa Marie; Chua, Enrique III
Ascaris infections lead to malnutrition and poor cognitive development especially to children aged 5-15 years of age. In the Philippines, protein-energy malnutrition is one of ten leading causes of child mortality. Ascariasis and the prevalence of protein energy malnutrition and relate it to the demographic factors such as age group, educational attainment of the mother, annual family income, availability of toilet, and proper hand washing practice.